Personality and Attitude : Exploring the Interconnection of Fisher’s Four Broad Temperament Dimensions with Evaluative Language Usage in Adolescents - Aalto, Pirkko (fi=Turun yliopisto|en=University of Turku|, 2018)
Today it is acknowledged that about 50% of the variations in human personality are connected to genetic factors. The brain systems driving human personality offer one possibility of exploring the biological basis of temperament. This diversity of the mind is at the heart of this research as its objective is to investigate the interconnection of one’s neurobiological basis of personality and one’s language usage in the region of attitude. The research was carried out by organizing a tripartite interview with a selected group of 9th grade adolescents in the spring of 2017 in their mother tongue, Finnish, and their foreign language, English. The interview consisted of themes from everyday life, of which one of its underlying themes, that of traveling, was chosen for analysis. It provided the research with an inspiring yet divisive theme in the search for a connection of one’s biological temperament and one’s way of expressing attitude. The interview offered a possibility to explore differences among the individuals in terms of their personality and language usage overall as well as across the three different parts to find out whether the personality types would express attitude differently and whether there would be any difference in the attitudes presented on the basis of the two languages used. The research at hand examined this interconnection by using Dr. Helen Fisher’s ([2009] 2011) Personality Type Test and Martin and White’s (2005) Appraisal framework for attitude. Fisher’s temperament construct measures the degree to which one is an Explorer, Builder, Director, and Negotiator, i.e. how one scales on the four broad brain systems, these being the dopamine, serotonin, testosterone, and estrogen systems. The relevance of these chemicals in human personality has been acknowledged. Martin and White’s Appraisal framework for attitude offers a tool for analyzing spoken language and attitude. In their model, attitude is divided into affect (emotion), judgement (ethics), and appreciation (aesthetics), all of the three having subcategories as well. The results showed that attitude was expressed differently depending on whether one was primarily an Explorer, Builder, Director, or Negotiator. This was visible both when looking at overall patterns of appraisal as well as the division among its three main categories. The results were also statistically significant. In terms of the tripartite interview, the overall results indicated there to be no difference in the language usage. Interestingly, the usage of the three main categories showed some difference: affect was the most used in the second part, whereas appreciation was more visible in the third part. Judgement, on the other hand, was divided among the two. The findings of the research opened a new venue for exploration in related scientific fields.